The Future of Amil Professionalization in Indonesia: Exploring Student Intentions - Anas Zahir Almasri; Maryam Batubara; Juliana Nasution; Muhammad Idris Nasution (Islam Realitas: Journal of Islamic and Social Studies, 2023)
The professionalization of amil (zakat manager) become an ongoing problem in zakat organizations and has received sharp criticism. This problem has begun to be addressed, among other things, by developing the zakat and waqf management study program (MAZAWA) in universities, but do the students themselves intend to pursue a career as professional amils in the future? This research was carried out to discuss such problems related on zakat management. The study was located at UIN Sunan Ampel, Surabaya, and IAIN Langsa, with 95 respondents. The data analysis technique uses descriptive statistics and SEM-PLS using SmartPLS 4.0 software, while to see the level of their intention to pursue a career as amil, a hypothetical statistical analysis technique is used. The research results show that the variables attitude toward the behavior (ATB) (2.608>1.98), perceived behavioral control (PBC) (1.989>1.98), and subjective norms (SN) (3.922>1.98) have a significant effect on students' intentions to pursue a career as an amil. The research results also show that MAZAWA students' intentions to have a career as amils are in the high category (1522 > 1.140 + (l.5x253,3)), so it can be said to have significantly supported efforts to professionalize amil in higher education. Their high intentions need to be supported by increasing the factors that influence them. Their high intentions need to be supported by increasing the factors that influence them; The financial benefits and professionalism of amil as a career need to be considered, the reach of beneficiaries and access to volunteering needs to be expanded, and outreach about amil careers needs to be further intensified.Problem profesionalisasi amil menjadi persoalan yang belum kunjung usai di organiasasi zakat dan mendapat kritik tajam. Persoalan ini telah mulai dibenahi, antara lain dengan pengembangan pendidikan program studi manajemen zakat dan wakaf (MAZAWA) di perguruan tinggi, namun apakah para mahasiswa sendiri memiliki intensi untuk berkarir sebagai amil profesional di masa depan? Untuk melihat bagaimana gambarannya, penelitian ini pun dilakukan. Penelitian berlokasi di UIN Sunan Ampel, Surabaya, dan IAIN Langsa, dengan jumlah responden sebanyak 95 orang. Teknik analisis data menggunakan SEM-PLS dengan software SmartPLS 4.0. Hasil penelitian menunjukkan bahwa variabel ATB (2.608>1.98), PBC (1.989>1.98), dan SN (3.922>1.98) berpengaruh signifikan terhadap intensi mahasiswa untuk berkarir sebagai amil zakat. Hasil penelitian juga menunjukkan bahwa intensi mahasiswa MAZAWA untuk berkarir sebagai amil zakat termasuk kategori tinggi (1522 > 1.140 + (l.5x253,3)), sehingga dapat dikatakan telah sangat mendukung upaya profesionalisasi amil zakat di perguruan tinggi. Tingginya intensi mereka perlu didukung dengan meningkatkan faktor-faktor yang mempengaruhinya; keuntungan secara finansial dan profesionalitas amil sebagai karir perlu untuk diperhatikan, jangkauan penerima manfaat dan akses untuk menjadi relawan perlu diperluas, dan sosialisasi tentang karir amil perlu lebih digencarkan lagi.